Epidemiology and Pathophysiology of Diverticular Disease - Munie, Semeret T.; Nalamati, Surya P. M. (Clinics in Colon and Rectal Surgery, 2018)
Colonic diverticular disease is a common health care issue which has historically been attributed to western countries and older age population. Recent studies have shown a rise in incidence among developing countries that have adopted western diets as well as rise in prevalence among younger patients. In this article, the authors discuss the incidence, epidemiology, and pathophysiology of colonic diverticular disease.
Keywords: diverticular disease; diverticulitis; colonic diverticula